The Effectiveness of Elsa Speak Application on Students’ Speaking Skills at Tenth Grade of Senior High School in Tarakan - Kusmaryani, Woro; Rahayu, Febrianti (Universitas Muhammadiyah Mataram, 2025)
English speaking skill is very crucial because this ability expresses thoughts, feelings, and ideas in real situations through a dynamic and interactive process for personal and professional purposes. Despite the growing integration of AI-based language learning applications in EFL classrooms, there is still limited empirical evidence on the effectiveness of the ELSA Speak application in improving the speaking skills. The purpose of this study was to investigate the effectiveness of using ELSA Speak application on speaking skill of 10th grade students of Senior High School in Tarakan. The method employed in this study was a pre-experimental. The sample of this study was class X-5 consisting of 33 students, who were selected through cluster random sampling. The stages of the study were pre-test, treatments, and post-test. Treatment was given for 5 meetings. The pre-test and post-test focused on testing English language skills in the aspects of pronunciation, grammar, vocabulary, fluency, and comprehension. Pre-test and post-test data were analyzed statistically using the non-parametric Wilcoxon Signed-Rank test. The results of the statistical analysis showed that the p-value of 0.00 was far below the operational standard of 0 05 with a Z score of -5.152 indicating that the treatments using ELSA Speak application showed a significant effect on speaking skill of 10th grade students of Senior High School in Tarakan. The 'study by topic feature in ELSA Speak application was the most effective feature in improving students' speaking skill because it provided contextual and relevant speaking exercises to real-life situations.